(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
The application of high-resolution X-ray computed tomography permits an appraisal of historically and newly collected specimens of Belosaepia (Belosaepiidae, Coleoidea, Cephalopoda) from the Ypresian (Early Eocene) of Belgium and provides resolution into the taxonomy of stem-group sepiids. The new finds are from the basal beds of the Egemkapel Clay Member (Tielt Formation) in the Ampe claypit at Egem and in the middle of the Roubaix Clay Member (Kortrijk Formation) in the Koekelberg claypit at Marke (province of West-Flanders, Belgium). Combining the historically and newly collected material allows us to conclude that only a single species can be positively identified, namely Belosaepia tricarinata (Watelet, 1851), and that all currently documented occurrences are restricted to the middle Ypresian (NP11-NP12). This seems to correspond well with the occurrence of Belosaepia tricarinata in the Paris, London, and Hampshire basins. Micro-CT imaging is an excellent, non-destructive tool in the study of the calcified remains. In the Belosaepia skeleton, this method allowed us to identify growth lines, ontogenetic changes, and resorption. Utilised in conjunction with a biostratigraphic assessment, this technology has the potential to be a major aid in taxonomic assignments and revisions. In the current study, it also highlighted stratigraphically important fossils (e.g. Nummulites) retained in the residual sediment attached to the specimens. This provides additional stratigraphic information that may otherwise be lost, or not recorded in older samples.